FORAMINIFERA AND OSTRACODES ACROSS THE PLIENSBACHIAN-TOARCIAN BOUNDARY IN THE ARCTIC REALM (STRATIGRAPHY, PALAEOBIOGEOGRAPHY AND BIOFACIES) - Nikitenko B.L.; Mickey M.B. (My University, 2004)
The analysis of samples from numerous Pliensbachian and Toarcian sections from the northern regions of Russia and northern Alaska, as well as published data, allow us to estimate the correlative significance of foraminifera and ostracodes, and to develop an Arctic zonal standard based on these microfauna. During the Late Pliensbachian-Early Toarcian depositional period in the Arctic Basin and northwestern seas of Western Europe, a succession of almost simultaneous biotic and abiotic events occurred: widespread development of black bituminous shale at the beginning of the Early Toarcian, and a microbiota crisis (mass extinction event) in the Northern Hemisphere. The Early Toarcian microbiotic crisis was very sharp in both Arctic and Western European palaeobasins. In the Arctic seas, the generic and family composition of ostracode communities was completely replaced by new taxa. The species composition of foraminiferal assemblages changed considerably, while the generic composition of the foraminifera is only characterized by partial changes. In the Western European seas, the Early Toarcian microbenthos crisis caused taxonomic changes generally at the species level among foraminifera and at the generic level among ostracodes. The comprehensive analysis of the biogeographical distribution of Late Pliensbachian and Early Toarcian foraminifera and ostracodes, as well as Jaccard cluster analysis, allow us to define several biogeographical units within the Arctic and Boreal-Atlantic realms. A pattern of ecological distribution of microbenthos in bathymetric zones in Siberian palaeobasins has been developed, providing the basis for palaeoenvironmental reconstructions.
Keywords: Toarcian; Pliensbachian; Mesozoic::Jurassic::Lower::Toarcian; Mesozoic::Jurassic::Lower::Pliensbachian; Мезозой::Юрская::Нижний::Плинсбахский; Мезозой::Юрская::Нижний::Тоарский